Positive Politeness Strategies At Google Review Post Caption - Natalia Dwi; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2024)
In the digital age, online platforms like Google Reviews have become significant spaces for individuals to express opinions and feedback. This study aims to investigate the linguistic and pragmatic aspects of positive politeness strategies utilized in the captions of these reviews. Positive politeness, a concept from politeness theory, involves linguistic strategies aimed at enhancing rapport and mitigating potential face-threatening acts. The research employs a qualitative approach, analyzing a diverse set of Google review post captions to identify prevalent positive politeness strategies. Through a detailed examination of linguistic features, such as lexical choices, syntactic structures, and discursive elements, the study seeks to unveil patterns and variations in the use of positive politeness. Additionally, the research delves into the socio-cultural context surrounding the reviews, considering factors that may influence language choices in this digital communication medium. By shedding light on the positive politeness strategies within Google review post captions, this study contributes to the broader field of pragmatics, offering insights into how individuals navigate politeness norms in the online domain. The findings may have implications for understanding online communication dynamics, customer feedback practices, and the role of positive politeness in shaping digital interactions within the context of review platforms like Google.